Monitoring Kelembaban Tanah pada Sistem Pentanahan (Grounding) Instalasi Rumah Tangga dengan Sistem Arang Aktif-Garam Berbasis Atmega 328 - Affan Bachri; Arief Budi Laksono; Achmad Fauzi Maulana (Universitas Islam Lamongan, 2022)
The recommended standard value of soil resistance is 0 – 5, Grounding is related to the earthing of electricity. Electricity is looking for all media that can be used to flow until it empties into the ground. Good grounding can prevent fire and electric shock. The grounding system is the most important thing in protecting the electrical installation system. The grounding system (grounding) functions as a channel for excessive current caused by disturbances or lightning strikes into the ground, SIGARANG is a grounding system that uses charcoal and salt as materials to improve the resistance value of the grounding soil. Addition of water, salt and charcoal the chemical reaction of NaCl with a copper grounding electrode results in an ionization process.